2019
DOI: 10.3389/feart.2019.00098
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Isotopic Evidence for Organic Matter Sulfurization in Redox Gradients Around Mangrove Roots

Abstract: Coastal environments like mangrove forests are increasingly recognized as potential hotspots for organic carbon burial, giving them a crucial and yet poorly constrained role in the global carbon cycle. Mangrove sediments are frequently anoxic, which facilitates elevated organic matter (OM) burial via several mechanisms, including sulfurizationabiotic reactions between dissolved (poly)sulfide and OM that decrease its lability. Although sulfurization was estimated to account for roughly half of OM preservation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…Sulfate excesses of up to 18% indicate that sul de is not always reoxidized in situ. Mangrove root xylem tissue on Little Ambergris Cay contains sulfate with 34 S/ 32 S nearly 30‰ lower than that of seawater sulfate, suggesting that the oxygenic mangrove roots facilitate sul de oxidation in the groundwater 26 . Sul dic groundwater dynamics on Little Ambergris Cay therefore differ from those in euxinic tidal ponds in ne-grained sedimentary environments, in which the delivery of oxidants are limited by diffusion and consequently the fraction of sul de that is reoxidized is low 27 .…”
Section: Controls On Mat Preservationmentioning
confidence: 98%
See 1 more Smart Citation
“…Sulfate excesses of up to 18% indicate that sul de is not always reoxidized in situ. Mangrove root xylem tissue on Little Ambergris Cay contains sulfate with 34 S/ 32 S nearly 30‰ lower than that of seawater sulfate, suggesting that the oxygenic mangrove roots facilitate sul de oxidation in the groundwater 26 . Sul dic groundwater dynamics on Little Ambergris Cay therefore differ from those in euxinic tidal ponds in ne-grained sedimentary environments, in which the delivery of oxidants are limited by diffusion and consequently the fraction of sul de that is reoxidized is low 27 .…”
Section: Controls On Mat Preservationmentioning
confidence: 98%
“…Inorganic carbon sources in this system include seawater DIC that has a δ 13 C value of ~0.85‰, ooid sand that has a δ 13 C value of ~5‰, and atmospheric CO 2 that has a δ 13 C value of ~-8‰ 15,28 . Organic matter in the microbial mats has a δ 13 C value of ~-13‰ 19,26 . In the shallowest porewater, which had the lowest DIC δ 13 C values (Fig.…”
Section: Controls On Mat Preservationmentioning
confidence: 99%
“…Low leaf  34 S values, for instance, the lowest value of 5‰ found in the unimpacted site -suggest that the most probable source of this 34 S-depleted S is sulfide oxidation, followed by mixing with seawater sulfate. Low  34 S values in mangrove root vascular tissues may indicate assimilation/oxidation of sulfide, potentially to reduce their toxic sulfide exposure (Fry et al, 1982;Raven et al, 2019), with reported isotope effect of -5.2‰ for non-biological oxidation of sulfide (Fry et al, 1988) and a smaller +1-3 ‰ effect for anaerobic oxidation of sulfide by photosynthetic bacteria (Fry et al, 1984).…”
Section: Mangrovesmentioning
confidence: 99%
“…As elements such as carbon (C), nitrogen (N) and sulfur (S) circulate in the biosphere, stable isotopic compositions of 13 C/ 12 C, 15 N/ 14 N and 34 S/ 32 S change in predictable ways due to mixing and fractionation, giving insights into sources and cycling of these elements (Fry 2006). SIA has been widely used in mangrove ecosystem studies to better understand food web interactions (Bouillon et al, 2008;Larsen et al, 2012;Bui and Lee, 2014;Abrantes et al, 2015), mangrove nutrient uptake (McKee et al, 2002), mangrove water use (Santini et al, 2015;Hayes et al, 2019), cycling of C (Maher et al, 2013a;Maher et al, 2017;Sasmito et al, 2020), N (Fry and Cormier, 2011), S (Raven et al 2019), and greenhouse gas emissions (Maher et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…As elements such as carbon (C), nitrogen (N) and sulfur (S) circulate in the biosphere, stable isotopic compositions of 13 C / 12 C, 15 N / 14 N and 34 S / 32 S can change in predictable ways due to mixing and fractionation, giving insights into sources and cycling of these elements (Fry, 2006). SIA has been widely used in mangrove ecosystem studies to better understand food web interactions (Bouillon et al, 2008;Larsen et al, 2012;Bui and Lee, 2014;Abrantes et al, 2015); nutrient uptake (Mc-Kee et al, 2002); water use (Santini et al, 2015;Hayes et al, 2019); cycling of C (Maher et al, 2013a(Maher et al, , 2017Sasmito et al, 2020), N (Fry and Cormier, 2011) and S (Raven et al 2019); and greenhouse gas emissions (Maher et al, 2013b). While traditional field methods such as measuring species composition to evaluate the structure and functioning of ecosystems can be time-consuming and expensive, SIA of ecosystem components can evaluate functional aspects of element cycling and food webs in a cost-effective way (Fry, 2006).…”
mentioning
confidence: 99%